Cardiac Rehabilitation: A Bibliometric Review From 2001 to 2020 - Yuan, Guozhen; Shi, Jingjing; Jia, Qiulei; Shi, Shuqing; Zhu, Xueping; Zhou, Yan; Shi, Shuai; Hu, Yuanhui (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular disease (CVD) is a serious threat to global public health due to its high prevalence and disability rate. Meanwhile, cardiac rehabilitation (CR) has attracted increasing attention for its positive effects on cardiovascular system. There is overwhelming evidence that CR for patients with CVD is effective in reducing cardiovascular morbidity and mortality. To learn more about the development of CR, 5567 papers about CR and related research were retrieved in the of Web of Science Core Collection from 2001 to 2020. Then, these publications were scientometrically analyzed based on CiteSpace in terms of spatiotemporal distribution, authors distribution, subject categories, topics distribution, references. The results can be elaborated from three aspects. First, the number of annual publications related to CR has increased year by year in general over the past two decades. Second, a co-occurrence analysis of the output countries and authors shows that a few developed countries such as US, Canada and UK are the most active places to carry out CR, and where regional academic communities represented by Sherry Grace and Ross Arena were formed. Third, an analysis of the subject categories and topics distribution of the papers reveals that CR is a typical interdiscipline with a wide range of disciplines involved, including clinical medicine, basic medicine, public health management, sports science. The research topics cover the participants and implementers, components, objectives and requirements of CR. The current research hotspots are the three core modalities of CR, namely patient education, exercise training and mental support, as well as mHealth depended on computer science. In conclusion, this work has provided some useful information for getting knowledge about CR, including identifying potential collaborators for researchers interested in CR, discovering research trends and hot topics of CR, which can offer some guidance for more extensive and in-depth CR-related studies in the future.